Socio-technical context for insertable devices - Heffernan, Kayla J.; Vetere, Frank; Chang, Shanton (Frontiers in Psychology, 2022)
In this paper we show that voluntarily inserting devices inside the body is contested and seek to understand why. This paper discusses insertables as a source of contestation. To describe and understand the social acceptability, reactions towards, and rhetoric surrounding, insertable devices the socio-technical framework is applied. It looks at (i) technical capabilities of insertable devices (the technical context), (ii) the reactions towards insertables (the social context) and (iii) the regulatory environment. The contribution of the paper is to give expiatory power to the misperceptions present in reactions to insertables. This contribution is theoretically proposed and needs to be empirically tested.